أثر الصادرات الزراعية وتقلباتها عل الأمن الغذائثي العربي الواقع الراهن والرؤى المستقبلية - الدكتور سالم توفيق النجفي (PROSPECTIVE RESEARCHES, 2023)
The effect between the rate of economic growth and exports is being exchanged and such a relationship is being effected by the fluctuations that took place in the exports revenues. Arab agricultural exports do not form a high relative importance except fish and fruit Econometric number for the performance of relative exports of the two goods mentioned above has reached about 13.03 and 3.04 respectively. Fluctuations that took place in the agricultural exports are bigger than its resemblances of agricultural important particularly the cereals. Half of the agricultural exports are concentrated in four Arab countries. Goods Structure indicates that 90% of the agricultural export are related to four goods grouping. Econometric analysis has confirmed that participation of agricultural exports in improving positions of Arab food security is limited inspite of its significance statistically. Also, it indicates that the effect between growth product and agricultural exports is exchangeable, though it is relatively low. It is unexpected to see increasing in exports revenues of the Arab exports on the threshold of 21st century under the economic climate of the GAAT.